2022
DOI: 10.7554/elife.71094
|View full text |Cite
|
Sign up to set email alerts
|

Placental uptake and metabolism of 25(OH)vitamin D determine its activity within the fetoplacental unit

Abstract: Pregnancy 25-hydroxyvitamin D [25(OH)D] concentrations are associated with maternal and fetal health outcomes. Using physiological human placental perfusion and villous explants, we investigate the role of the placenta in regulating the relationships between maternal 25(OH)D and fetal physiology. We demonstrate active placental uptake of 25(OH)D3 by endocytosis, placental metabolism of 25(OH)D3 into 24,25-dihydroxyvitamin D3 and active 1,25-dihydroxyvitamin D [1,25(OH)2D3], with subsequent release of these met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…To identify interspersed repetitive elements bearing hallmarks of activating regulatory potential in human trophoblast, we performed H3K27ac profiling using either ChIP-seq or CUT&Tag (Kaya-Okur et al, 2019). We analysed our previously published data from primary human cytotrophoblast (Ashley et al, 2022), as well as newly generated data from cytotrophoblast-like human trophoblast stem cells (hTSCs) (Okae et al, 2018), which can be differentiated in vitro and allow for easy genetic manipulation (Figure 1A). Using the Repeatmasker annotation (excluding simple and low complexity repeats), we determined the frequency of H3K27ac peaks per repeat family, and compared it to random controls using a permutation test (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify interspersed repetitive elements bearing hallmarks of activating regulatory potential in human trophoblast, we performed H3K27ac profiling using either ChIP-seq or CUT&Tag (Kaya-Okur et al, 2019). We analysed our previously published data from primary human cytotrophoblast (Ashley et al, 2022), as well as newly generated data from cytotrophoblast-like human trophoblast stem cells (hTSCs) (Okae et al, 2018), which can be differentiated in vitro and allow for easy genetic manipulation (Figure 1A). Using the Repeatmasker annotation (excluding simple and low complexity repeats), we determined the frequency of H3K27ac peaks per repeat family, and compared it to random controls using a permutation test (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential of hTSC-active ERVs to drive trophoblast gene expression, we first asked whether some functioned as gene promoters. Using our primary cytotrophoblast RNA-seq data (Ashley et al, 2022), we performed de novo transcriptome assembly and extracted transcripts for which an ERV from the selected families overlapped the transcriptional start site. In line with the relative small proportion of H3K4me3-containing elements (Figure 1E), we identified few ERVs with apparent promoter activity (Supplementary Table S2).…”
Section: Htsc-active Ervs Lie Close To Genes With Preferential Tropho...mentioning
confidence: 99%
“…This compound was thought to pass into the fetus by passively diffusing across the placenta ( Greer et al, 1984 ; Hollis and Wagner, 2013 ). Now, in eLife, Jane Cleal from the University of Southampton and co-workers – including Brogan Ashley and Claire Simner as joint first authors – report that the amount of vitamin D the fetus receives is actually regulated by the placenta actively taking up and breaking down 25(OH)D ( Ashley et al, 2022 ).…”
mentioning
confidence: 99%
“…These altered angiogenic pathways, in combination with the correlation of human placental gene expression of amino acid transporters with maternal Vit-D status and Vit-D binding protein reported by Cleal et al [ 123 ], imply that Vit-D indeed mediates fetal nutrient supply via the placenta [ 124 ]. Adding more complexity to these biological mechanisms, Ashley et al demonstrated experimental data of an active placental uptake of maternal 25(OH)D 3 placental metabolism into active metabolites and their subsequent active release into both maternal and fetal compartments, suggesting that fetal Vit-D supply is not only dependent on its availability to the placenta, but also on placental function itself [ 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%